Invention of Xani’s Mem û Zin As a Fundamental Work in Kurdish National Canon - Zülküf Ergün (Nubihar Akademi)

(untitled)
Although the canonization of literary and non-literary works is an old phenomenon, the national canon appears in modern period with spread of nationalism and foundation nation state. In this canon some particular literary works are chosen in order to show existence and continuity of a nation and this work is strengthened as representation of national character by various literary commentaries. We also witness the efforts on the part of Kurdish intellectuals to construct a national canon from the start of spread of idea of nationalism. Within this framework, Xani’s Mem û Zin emerged as the fundamental source of the national canon and Xani as the forerunner of Kurdish national thought.Although this thought first presented itself in a poem of Haci Qadri Koyi, it was systematized in later Kurdish journals and newspapers owing to the intellectual efforts of some members of Bedirxani family. Shortly thereafter, this thought was reinforced through various printings of Mem   Zin, anthologies and histories of Kurdish literature and publications of literary and academic works on this topic. For this reason, Xani’s Mem   Zin has been accepted as the first work of national canon both in fields of politics and literature and in society more broadly.